Evaluation of the DNA damaging potential of indigenous health hazardous quartz nanoparticles on the cultured lung cells. Issue 2 (9th January 2017) - Sushma; Kumar, Hridyesh; Ahmad, Iqbal; Dutta, Pradip Kumar
Graphical Abstract: Abstract: Quartz nanoparticles (QNPs) cause various diseases in the biological systems and are thus considered as hazardous materials; however, their properties are important in a wide range of biological and pharmaceutical entities. The present study was initiated to enhance the understanding of the genotoxic potential and focused on the mechanism involved in the indigenous quartz nanoparticles induced toxicity in A549 cells. The results show a concentration dependent decrease in the cell viability of A549 cells. Additionally, QNPs exposure results in the concentration dependent toxicity, which intensifies the generation of ROS, which in turn is confirmed by the increased lipid peroxidation and decreased GSH levels. Moreover, it also induces DNA damage in the cells exposed to QNPs as compared to the control cells. The outcome of the results confirms that QNPs have cytotoxic and genotoxic effects on the A549 cells in a concentration and time dependent manner. Western blot analysis indicates the up regulation of LC-3I/II, Beclin-1, and p62 protein levels, which confirms the occurrence of autophagy through the phosphatidylinositol 3-kinase (PI3K)/a threonine kinase (Akt)/mammalian target of rapamycin (mTOR) pathway, as well as the inhibitor of autophagy is also verified. Our study demonstrates that QNPs exposure in human lung cells causes oxidative stress and DNA damage, which leads to autophagy. Hence, from a bioremediation point of view, the remedial strategy that can be adopted from the biological DNA damage from these health hazardous materials will result in a safer environment.